2015
DOI: 10.1103/physreva.92.012313
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement dynamics of quantum oscillators nonlinearly coupled to thermal environments

Abstract: We study the asymptotic entanglement of two quantum harmonic oscillators nonlinearly coupled to an environment. Coupling to independent baths and a common bath are investigated. Numerical results obtained using the Wangsness-Bloch-Redfield method are supplemented by analytical results in the rotating wave approximation. The asymptotic negativity as function of temperature, initial squeezing and coupling strength, is compared to results for systems with linear system-reservoir coupling. We find that due to the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
(87 reference statements)
0
2
0
Order By: Relevance
“…The dynamics of a nanoparticle that nonlinearly couples to its reservoir has been theoretically studied in the Markovian regime. [18,19] Non-Markovian theory plays an important role in treating a realistic system. The non-Markovian environment usually can keep the coherence and suppress the dissipation.…”
Section: Introductionmentioning
confidence: 99%
“…The dynamics of a nanoparticle that nonlinearly couples to its reservoir has been theoretically studied in the Markovian regime. [18,19] Non-Markovian theory plays an important role in treating a realistic system. The non-Markovian environment usually can keep the coherence and suppress the dissipation.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the decoherence caused by a common environment can play a constructive role in generating stable entanglement between two quantum systems [9][10][11][12]. The intrinsic physics is the existence of the decoherence-free state (DFS) [13][14][15], which triggers the enthusiasm of relearning the role of decoherence of composite system caused by a common environment from different systems such as harmonic oscillators [16][17][18][19][20] and spins [21][22][23][24], and different environments such as crystal chains [25][26][27] and waveguides [23,24,[28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%